Analysis Of Inhibition Of Fertilizer Unloading Process Bulk Urea In MV.Abusamah At The Pier Tanjung Wangi Banyuwangi - Kodrat Alam; Muhammad Mahdi; Trio Adi Rohmanto (IWJ : Inland Waterways Journal, 2022)
The delay in the process of unloading bulk urea is a problem that often occurs at PT. Pupuk Indonesia Logistik, especially in MV. Abusamah is one of the ships owned by PT. Pupuk Indonesia Logistik. In the activity of unloading bulk urea fertilizer at the Tanjung Wangi pier, Banyuwangi MV.Abusamah often experiences delays, this can cause losses for the company. This research purpose to determine the factors causing the delay in the process of unloading bulk urea fertilizer and the efforts made to prevent it. The research method used is descriptive qualitative research method. Sources of research data taken from primary data and secondary data. Data collection techniques by observation, interviews and literature study. From the results of the study, there are several factors that affect the delay in the process of unloading urea in MV.Abusamah at the Tanjung Wangi pier, Banyuwangi and several efforts that have been made by the company in overcoming these problems. The conclusion is implementation of the process of unloading urea fertilizer at the Tanjung Wangi pier in Banyuwangi by MV.Abusamah is often hampered because it is influenced by several factors, namely inadequate unloading equipment, weather factors, namely rain, and limited capacity land conveyor. Efforts were made to delay the unloading of bulk urea fertilizer by increasing the number of transportation facilities, namely trucks which are one of the supporting tools in unloading activities, sending updated weather forecast news from BMKG to the DPA/HSSE department, and adding storage warehouse capacity.